THE SOURCES OF SUPPLY OF FRUITS AND VEGETABLES IN NOVI SAD (SERBIA) - Tamara LUKIĆ; Ivana BLEŠIĆ; Milka BUBALO ŽIVKOVIĆ; Dajana BJELAJAC; Bojan ĐERČAN; Tatjana PIVAC; Sanja KOVAČIĆ (Analele Universităţii din Oradea: Seria Geografie, 2023)
The paper talks about the facts that were established in the research of the origin of fruits and vegetables in the markets of Novi Sad. The results of the research are presented using graphic and cartographic methods. Observed illogicalities are clarified in communication with consumers and sellers. The obtained results were compared with foreign works. One of the goals of the work was to determine the extent of suburban agriculture, which should be the most competitive with others further away from the city. Economic factors have a decisive influence from where the city will be supplied with fruits and vegetables.